(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the current state of energy cooperation between Turkey and Iraq and its place within the processes of regional security and economic integration. In particular, it examines the Kirkuk–Ceyhan oil pipeline, the exchange of electricity, cooperation in the natural-gas sphere, and the strategic significance of the “Development Road” project. The study analyzes the political, economic, and geostrategic factors of the energy relations between the two states and assesses the prospects for developing sustainable energy cooperation.